Penghilangan Senyawa Hidrogen Sulfida (H2S) Pada Biogas Menggunakan Kompos - Mahmud Azis Angkat; Muhammad Haikal Pasha; Asri Gani (Universitas Syiah Kuala, 2020)
Biogas prior to use must be purified first from the content of hydrogen sulphide (H2S) which although small in number but can cause losses due to corrosion of the metal. This compound when burned will form sulfur dioxide (SO2) or sulfur trioxide (SO3) known as SOx substances that can cause acid rain. H2S removal can be done by means of biofilter process. The biofilter media used in this research was compost with size variation (8-25 mesh, 25-40 mesh, and 40-60 mesh) and mass variation (0.75 kg, 1 kg, 1.5 kg, 1.75 kg, and 2 kg). The concentration of H2S gas feed into the biofilter column is 493 ppm with contact time of 60 minutes. The concentration of H2S gas before and after passing through the biofilter column were analyzed using Gas Analyzer The results showed that the maximum absorption capacity and maximum absorption efficiency compost in a row that is equal to 19,894 mgH2S/gr compost and 94,73%.